Vaccine hesitancy among health paraprofessionals: A mixed methods study - Madeline Hergott; Michael Andreski; John Rovers (PLoS ONE, 2025)
Background The World Health Organization (WHO) defines vaccine hesitancy as “a delay in acceptance or refusal of vaccines despite availability of vaccination services”. Vaccine hesitancy has also been declared a top threat to global health. Some employers imposed vaccine mandates during the Covid-19 pandemic resulting in health care employees resigning or being fired rather than receive a vaccine. Healthcare paraprofessionals such as certified nursing assistants, dietary and home health aides are among the most patient facing of all health care providers. Their beliefs and attitudes about vaccines are critical to how they communicate about vaccines with their patients. Objective The objective of this project was to survey health care paraprofessionals to explore their thoughts and opinions about vaccines in general, and Covid-19 vaccines specifically. Methods This was a 25 question, mixed methods, cross sectional email survey. Subjects were recruited from the mailing list of a non-profit organization in the Midwest. This organization is dedicated to bringing a face and a voice to healthcare paraprofessionals engaged in direct patient care. Results Most respondents were reasonably well informed about vaccines; had received one or more doses of indicated vaccines; used credible resources to learn about vaccines and believed physicians and pharmacists were the most trusted information sources. Qualitative results indicated that respondents expressed support for vaccines but that the support was often qualified in that a respondent may have had both pro and anti-vaccine opinions in the same response. They also expressed that communications about vaccines were often problematic. Additional vaccine-related continuing professional development for healthcare paraprofessionals appears to be indicated. Conclusions Although attitudes towards vaccines were generally positive, respondents had concerns about the quality of vaccine information. Additional vaccine-related continuing professional development for healthcare paraprofessionals appears to be indicated.